Microbial Contamination of Date Rutab Collected from the Markets of Al-Hofuf City in Saudi Arabia - Siddig H. Hamad; Farag A. Saleh; Mutlag M. Al-Otaibi (The Scientific World Journal)
The microbial contamination of 60 samples from six date cultivars in the rutab stage purchased from different retail outlets in AL-Hofuf City, Saudi Arabia was studied. All samples were found contaminated with aerobic mesophilic bacteria at loads in the order 102 to 105 cfu/cm2 with some significant differences among varieties that can be attributed to differences in the weather conditions during rutab season. Also all samples, except only one, were contaminated with molds and yeasts at loads in the order 102 to 103 cfu/cm2. Potentially pathogenic Staphylococcus aureus was detected in 57 samples and A. flavus/parasiticus in 13 samples, while coliforms were detected in 39 samples.